Heavy metal ions removal by lignocellulosics materials derived from Sago Bark and leaves - Ling, Chian Ye. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Lignocellulosics materials derived from sago bark and leaves are available in abundance and cheaply. In this study, sago leaflet, leaf stalk, and bark were characterized chemically and physically and used in the removal of lead(ll), copper(lI), and nickel(lI) ions from aqueous solutions. Two types of experimental apparatus were being used, equilibrium and column experiments. All the adsorbent samples varied considerably in their adsorption capacities. The metal adsorption capacity of all the adsorbent samples for different metals in both types of experiments were found to be in the order: Pb>Cu>Ni. The effects of solution pH, particle size of adsorbent and initial metal concentrations on the adsorption of heavy metal ions from aqueous solutions were also studied. Heavy metal ions adsorption capacities of all adsorbent samples were observed to be affected by these factors. The adsorption equilibrium data were observed to fit the Fruendlich model better than the Langmuir model. Kinetic studies showed that the sorption rates could be described well by the pseudo second-order kinetic equation.